Antimicrobial Resistance Patterns and Extended Spectrum Beta-Lactamases Producing MRSA Isolated From Wounds and Burns of Iraqi Patients - Issraa Hamza Yassin (Journal of Global Pharma Technology, 2019)
A total of 160 samples included 61 wounds samples and 99 burns samples were collected from Baghdad province hospitals. All samples were cultured on blood agar and mannitol salt agar plates to isolate     S. aureus bacteria. Results showed that rate of S. aureus isolates was 59% of wounds samples and 82.8% of burns samples. MRSA rate of S.aureus wounds and burns isolates was 58.3% and 93.9% respectively. Antibiotic susceptibility test showed that there was no resistance (0%) in ciprofloxacin, vancomycin and imipenem for all isolates, low levels of resistance were recorded for several antibiotics: trimethoprim 5%, rifampin 7.5%, chloramphenicol 7.5%, gentamicin 7.5%, levofloxacin 10% and cefotaxime 17.5%. High and moderate levels of resistance were recorded against cefepime with 82.5%, cefoxitin with 61%, piperacillin with 42.5%, ceftazidime with 27.5%, azithromycin with 25% and amoxicillin/clavilonicacid with 2.5%. 29 different patterns of resistance to 15 different antibiotics were observed as resistance profiles. High rate of 58% of total MRSA isolates was ESBLs producing isolates.